Growing managers : moving from team member to team leader - Ellington-Booth, Brenda; Cates, Karen L. ([London] : SAGE, 2016)
This case describes a newly promoted middle manager in a global, multi-cultural organization who is challenged by a number of factors in the workplace which are impacting her and her team's ability to perform. While it would be easy to blame the new manager, deeper analysis in fact reveals that many forces are at work here in addition to her inexperience, including communication of strategy and performance objectives, mismanaged team members, cultural inconsistencies and a lack of leadership direction and/or skill from the very top.
Originally Published in: Ellington-Booth, B., & Cates, K.L. (2012). Growing Managers: Moving from Team Member to Team Leader. 5-411-757. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Executive ability -- Case studies; Middle managers -- Case studies; Decision making -- Case studies; Organizational behavior -- Case studies